Analisis Strategi Pemasaran Dengan Metode Penjualan Langsung Pada Penjualan Produk “Soyy Milk” - Elsa Sefrillia; Mochamad Fatchurrohman; Yuvi Septia Ardhana; Reshita Putri maharani; Natalia Margaretha (Jurnal Hilirisasi Pengabdian Masyarakat, 2024)
This study evaluates the marketing strategy of soy milk products "SOYY MILK" with a focus on packaging innovation and direct sales methods. In addition, this evaluation aims to make it easier for business owners to make plans and decisions about this business in the future. Through a qualitative descriptive approach, the study was conducted for 3 months, exploring an in-depth understanding of the "SOYY MILK" group, its products, and the marketing strategies implemented. For the research subjects of Soyy Milk business owners, namely four students who are in the fifth semester of STIE Mahardhika Surabaya. The object of this study is the soy milk product "Soyy Milk". This research was conducted in the Soyy Milk production kitchen. Data collection through interviews, observations, and documentation using source triangulation techniques. The results show the success of direct sales strategies and internet marketing through social media, especially in reaching young consumers. Innovation in packaging also provides positive encouragement. In conclusion, the combination of direct sales strategies and internet marketing is effective in marketing "SOYY MILK," which is recognized by positive acceptance from consumers.